Advances in the economic analysis of participatory and labor-managed firms. Vol. 13 - Bryson, Alex; DeVaro, Jed (Advances in the economic analysis of participatory and labor-managed firms., 2012)
With the financial crisis and Great Recession, some economists have begun to question the orthodox approach to production and capital/labor relations over the last two to three decades. This orthodoxy has been thrown into question due to concerns of poor corporate decision-making, corporate capture of regulators, perceived rewards for failure, and uneven productivity growth. But a new spirit of introspection and doubt about orthodox approaches has created some impetus leading to greater interest in themes, such as worker ownership, sharing rewards, co-operatives, and employee involvement practices which feature heavily in the Advances series. This "new spirit" is apparent for all to see in the 12 contributions to this volume of Advances which cover co-operatives; effects of worker participation on firm performance; the diffusion of high involvement management practices; and outcomes for workers (i.e., job satisfaction and wages).